Purpose-driven branding in a country with economic turmoil: An investigation into the impact of purpose-driven brands on brand choice in the homecare category - Radebe, Silindile Nolwazi (The IIE, 2022)
The pressure for brands to be purpose driven has only been increased and accelerated by the COVID-19 pandemic but is this a possibility in a country facing economic turmoil, being unable to recover from the 2009 global recession. Purpose led brands have experienced positive, rapid growth which these brands have been able to sustain but this growth has been experienced outside of South Africa, mostly in the west. This is due to a wave of new customers, made up of millennials and Gen Z, who are demanding brands to pioneer and spearhead brand citizenship through fair business practices and environmental sustainability. To measure whether this phenomenon exists in South Africa, a quantitative, cross sectional study was undertaken measuring the influence of brand purpose on purchasing and consumption decisions by income earning millennials in Johannesburg, South Africa. The researcher found that in a volatile economic landscape such as South Africa, price and value for money are the primary motivators behind their brand choice and this is over and above brand marketing and advertising activities. These findings illuminate that a regions economic state can add or detract from an individual’s ability to act on their moral imperative.
Keywords: Brand purpose; Sustainability; Consumer behavior; Brand loyalty